Get the truth : former CIA officers teach you how to persuade anyone to tell all /: former CIA officers teach you how to persuade anyone to tell all. (2015) - Houston, Philip; (CIA officer), Floyd, Michael; Carnicero, Susan; Romary, Peter
No abstract available